Process Performance of Secondary Effluent Granular Media Filtration with and without Preozonation. (1st July 2015) - Merlo, Rion; De Las Casas, Carla; Henneman, Seppi; Witzgall, Robert; Yu, William; Ramberg, Steve; Parker, Denny; Ohlinger, Kurt
ABSTRACT: : A 10‐month pilot study compared the performance of conventional granular media filtration (CGMF) with granular media filtration with preozonation (OGMF) to determine the effects of preozonation on filter performance. Filtration recoveries were lower for OGMF compared to CMGF when operated at a loading rate of 18.3 m/h. Operation at 18.3 m/h met turbidity requirements for California Department of Public Health Title 22 unrestricted reclaimed water requirements for both OGMF and CGMF. Preozonated secondary effluent at a transferred dose of 3 mg/L resulted in an increase in ultraviolet transmissivity (UVT) of approximately 6% and greater than 5‐log inactivation of male‐specific bacteriophage MS2. Wet weather flow events resulted in UVT decrease and a decline in MS2 inactivation to less than 3 log attributed to higher ozone demand in the secondary effluent. Preozonation increased N‐nitrosodimethlyamine (NDMA) concentration approximately 10 times, but subsequent filtration reduced levels to secondary effluent values. A net increase in NDMA was observed at times.